The development of knowledge-shelf to enable an effective set-based concurrent engineering application. - Suwanda, Supriana (Cranfield University, 2019)
This research thesis presents the development of the Knowledge-Shelf (K-Shelf), a novel knowledge environment concept to support designers throughout Set- Based Concurrent Engineering (SBCE) application. The K-Shelf concept introduces a baseline model to understand the dimensions of knowledge environment in SBCE application as well as its synthetisation with acclaimed SBCE process model as the contribution to knowledge. The K-Shelf concept incorporates three steps of Knowledge Life Cycle (KLC) that comprises of knowledge capture, knowledge representation and knowledge provision. The K- Shelf concept also has three capabilities that supports the set of conceptual design generation, dynamic knowledge capture of design rationale with 5 Whys approach and the comparisons among set of design solutions with Trade-Off Curve (TOC) visualisation. To demonstrate these capabilities, a web-based software is developed based on Rapid Application Development (RAD) approach. Rigorous research methodology is employed to develop the K-Shelf concept. A systematic literature review is applied to capture the current approaches of knowledge environment in SBCE application. Two industrial case studies of Surface Jet Pump (SJP) and Brake Pedal Box (BPB) are presented to validate the K-Shelf concept. Furthermore, two expert judgements were also obtained. Thus, it was established that the K-Shelf is a knowledge environment to enable an effective SBCE application.
Keywords: Product development; knowledge environment; knowledge provision; design rationale; trade-off curve; surface jet pump; brake pedal box